El proyecto sociocultural de la izquierda chilena durante la Unidad Popular. Crítica, verdad e inmunología política - Martín Bowen Silva (Nuevo mundo - Mundos Nuevos, 2008)
The object of this research is the identification and analysis of the Chilean left-wing cultural project, as it was first thought of by intellectuals and authors supporters of the “Unidad Popular”government (1970-1973). It is proposed that the main element of this project resided in the willingness to create autonomous, critical social beings, an endeavor which struck deep into both cultural work creation and the way chilean identitary narrative and the popular subject appealed to left-wing militants and intellectuals. It is thus evidenced how a model of intellectual production, albeit its left-wing militancy, played an assisting role in distancing these politics from the popular world. On a different matter, it is hinted that culture –as a project– played an important, decisive role in the chilean revolutionary process, apart from the active part it may have played during the three years of Salvador Allende’s government.